Freedom Christian and Muslim Perspectives. - Mosher, Lucinda (Georgetown University Press, 2021)
The essays, historical and scriptural texts, and reflections in Freedom: Christian and Muslim Perspectives consider how these two faith communities have historically addressed freedom, providing needed context for deeper understanding of interfaith relations from ancient to modern times.